2015
DOI: 10.1111/ijal.12101
|View full text |Cite
|
Sign up to set email alerts
|

The effects of degrees of Dutch accentedness in ELF and in French, German and Spanish

Abstract: In a verbal guise experiment, 178 listeners with three nationalities (58 French, 59 German and 61 Spanish) listened to samples recorded by female speakers with three degrees of accentedness (strong/slight accented-Dutch and native) in English, French, German and Spanish. Findings indicate that a strong accent had a detrimental effect on understanding and attitudinal evaluations, while a slight accent hardly led to negative effects. A speaker with a strong Dutch accent in English was evaluated as less compete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
30
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 17 publications
(45 citation statements)
references
References 51 publications
(93 reference statements)
4
30
3
Order By: Relevance
“…However, Munro & Derwing (1995a, p. 305) established that "Although strength of foreign accent is indeed correlated with comprehensibility and intelligibility, a strong foreign accent does not necessarily cause L2 speech to be low in comprehensibility or intelligibility". Yet other studies have found no differences in comprehensibility due to degrees of accentedness (Hendriks et al, 2015;Munro & Derwing, 1995b;Nejjari et al, 2012).…”
Section: Introductionmentioning
confidence: 70%
See 4 more Smart Citations
“…However, Munro & Derwing (1995a, p. 305) established that "Although strength of foreign accent is indeed correlated with comprehensibility and intelligibility, a strong foreign accent does not necessarily cause L2 speech to be low in comprehensibility or intelligibility". Yet other studies have found no differences in comprehensibility due to degrees of accentedness (Hendriks et al, 2015;Munro & Derwing, 1995b;Nejjari et al, 2012).…”
Section: Introductionmentioning
confidence: 70%
“…Stibbard and Lee (2006) found that non-native listeners with a different L1 than the speaker did not differ from native listeners in their evaluations of the intelligibility of low-proficiency speakers versus high-proficiency speakers. Hendriks et al (2015) found that non-native listeners with a different L1 background than the non-native speaker were able to distinguish a strong non-native accent, but did not distinguish a slight non-native accent from a native accent. In terms of evaluations, the strong non-native accent was evaluated less positively by those non-native listeners than the slight and the native accent, but there were no differences between the slight and the native accent.…”
Section: Introductionmentioning
confidence: 90%
See 3 more Smart Citations